МІНІМІЗАЦІЯ ВИПАДКОВОЇ ПОХИБКИ ЦИФРОВОГО МЕТОДУ ВИМІРЮВАННЯ АМПЛІТУДИ СИНУСОЇДАЛЬНОГО СИГНАЛУ - Борщов, П.І. (Інститут електродинаміки Національної академії наук України, 2022)
The errors of measuring the amplitude of sinusoidal signals by the method based on the calculation of the sum of the ratios of digital samples of instantaneous signal values ​​to the sines of the phase angles corresponding to the sampling moments are investigated. A mathematical expression for determining the total random measurement error using the values of the parameters of the error components is obtained. It is shown that there is a minimum value of the total random measurement error as a function of the number of instantaneous signal values taken into account. The method of ensuring the reduction of the level of random error to the desired level is given. The method can be used to create metrological support for measuring the parameters of electrical signals at low and infralow frequencies, including industrial frequency. References 6, figures 4, table 1.